Conditions for a submanifold $F^n$ from $E^{n + p}$ to lie in $E^{2n − 1}$ - Nasedkina, Ya. S. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We consider a submanifold $F^n$ with $n$ principal directions in the space $E^{n + p}$, where $p ≥ n_1$.